Application of fluorescence in situ hybridization in the detection of bladder transitional-cell carcinoma: A multi-center clinical study based on Chinese population - Liqun Zhou; Kaiwei Yang; Xuesong Li; Yi Ding; Dawei Mu; Hanzhong Li; Yong Yan; Jinyi Li; Dongwen Wang; Wei Li; Yulong Cong; Jiangping Gao; et al. (Asian Journal of Urology)
Objective: To evaluate the diagnostic value of fluorescence in situ hybridization (FISH) in bladder cancer. Methods: We enrolled healthy volunteers and patients who were clinically suspected to have bladder cancer and conducted FISH tests and cytology examinations from August 2007 to December 2008. Receiver operating characteristic (ROC) curve analysis was performed and the area under curve (AUC) values were calculated for both the FISH and urine cytology tests. Results: A cohort of 988 healthy volunteers was enrolled to establish a reference range for the normal population. A total of 4807 patients with hematuria were prospectively, randomly enrolled for the simultaneous analysis of urine cytology, FISH testing, and a final diagnosis as determined by the pathologic findings of a biopsy or a surgically-excised specimen. Overall, the sensitivity of FISH in detecting transitional-cell carcinoma was 82.7%, while that of cytology was 33.4% (p < 0.001). The sensitivity values of FISH for non-muscle invasive and muscle invasive bladder transitional-cell carcinoma were 81.7% and 89.6%, respectively (p = 0.004). The sensitivity values of FISH for low and high grade bladder cancer were 82.6% and 90.1%, respectively (p = 0.002). Conclusion: FISH is significantly more sensitive than voided urine cytology for detecting bladder cancer in patients evaluated for gross hematuria at all cancer grades and stages. Higher sensitivity using FISH was obtained in high grade and muscle invasive tumors. Keywords: Bladder transitional-cell carcinoma, Fluorescence in situ hybridization, Detection, Grade, Stage